Managing the Transition to an Open Scholarly Literature - Neylon, Cameron (Septentrio Conference Series, 2014)
>> See video of presentation (62 min.) The question of radical change in the scholarly literature has shifted in the past 12 months from ‘if’ to ‘how’. There is growing consensus on the need for change alongside increasing action from funders and institutions aimed at driving those changes. However there is less consensus on what the ultimate end state will look like and how to get there. In particular two challenging collective action problems exist: how to manage the diversion of money from subscription budgets into the development, maintenance and running of a web-native communications infrastructure, and how to simultaneously encourage the cultural changes required in the research community to take advantage of the opportunities that infrastructure will bring. These two challenges are both tightly coupled with each other and with our vision of the ideal state of scholarly communications infrastructure. I will seek to chart out the various visions of the future alongside a model of how to drive the cultural and economic changes that can realise those visions in practice.